White Matter Lesions and Cognitive Impairment as Silent Cerebral Disease in Hypertension - Cristina Sierra; Antonio Coca (The Scientific World Journal)
Although the pathogenesis and clinical significance of cerebral white matter lesions remain controversial, it is well established that age and hypertension are the most important factors related to the presence of these lesions. Hypertension is known to be the most important factor for developing stroke and vascular dementia. In addition, the presence of cerebral white matter lesions is an important prognostic factor for the development of stroke, and also for cognitive impairment and dementia. The mechanisms underlying hypertension-related cognitive changes are complex and are not yet fully understood. Correlations between cerebral white matter lesions and elevated blood pressure provide indirect evidence that structural and functional changes in the brain over time may lead to lowered cognitive functioning when blood pressure control is poor or lacking.Some authors have suggested that the presence of white matter lesions in hypertensive patients could be considered an early marker of brain damage.